2008
DOI: 10.1016/j.juro.2008.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life in Patients Treated With Multimodal Therapy for Prostate Cancer

Abstract: Purpose: Patients with prostate cancer and high risk disease characteristics may benefit from multimodal therapy. However, the effects of multimodal therapy on health related quality of life have not been comprehensively described. We further characterized health related quality of life in patients treated with multimodal therapy. Materials and Methods: Patient data were obtained from the CaPSURE™ database, a national disease registry of men with prostate cancer. Included patients received active primary thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…9,20,21 The CaPSURE cohort reported higher pretreatment and posttreatment erectile dysfunction (42% [95% CI, 40%–44%] and 78% [95% CI, 76%–80%] of men, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,20,21 The CaPSURE cohort reported higher pretreatment and posttreatment erectile dysfunction (42% [95% CI, 40%–44%] and 78% [95% CI, 76%–80%] of men, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment refinements, such as nerve-sparing techniques, can mitigate erectile dysfunction consequences of prostate cancer treatment, while other treatment variations, such as use of neoadjuvant hormone therapy, 9 can adversely affect sexual outcome. Although associations of these and other factors with patient-reported sexual outcome have been studied, 3,1013 information regarding how the combination of pretreatment patient characteristics and treatment factors relate to individualized sexual outcome remains limited.…”
mentioning
confidence: 99%
“…Several studies have shown increased genitourinary and gastrointestinal toxicity from additional RT after RP [ 22 , 24 26 ]. In the South West Oncology Group trial, adverse events were more likely to occur in the RP + RT arm compared with the RP arm (23.8 % vs 11.9 %), including urethral strictures (17.8 % vs 9.5 %), total urinary incontinence (6.5 % vs 2.8 %), and rectal complications (3.3 % vs 0 %), respectively [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that HRQoL in men with localised prostate cancer tend to deteriorate within the first 12 months after diagnosis and that urinary and sexual functions recovery generally occurs within 2 years after virtually all treatments (Huang et al 2010), patients with ≤12 or ≥24 months of follow-up were excluded of this study for homogeneity. The same occurred for those under major life events and morbidity, disease progression/recurrence or under multimodal therapy (Wu et al 2008).…”
Section: Discussionmentioning
confidence: 69%